PHYSICO-CHEMICAL AND PROTOLITICAL PROPERTIES OF SILICA MODIFIED WITH PROPYLTHIOETHYLEAMINE: UDC 541.183.04:543.3 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2014)
Silica chemically modified by propylthioethyleamine was synthesized, their protolytic properties and application as an adsorbent for the removal of ions Pd(II) has been investigated. This ligand was grafted to the silica surface with two different routes: (1) as one-step reaction of silanization(homogeneous procedure, SiO2-SN(homo)); (2) as multistep chemical modification of silica, usingmercaptopropyltriethoxysilane, followed by aminoagent to convert the grafted surface SH-group to aminomoieties (heterogeneous procedure,SiO2–SN(het)). The new solids were characterized by FTIR and diffuse reflectanceUV-visspectroscopy. It was shown that a combination of pH-metric and conductometricmethods can generally picture of the grafted groups presence in the surface of SiO2.The amount of propylthioethyleaminegroups grafted on the SiO2-SN(homo) and SiO2–SN(het)is found 1.05 mmol/g and 0.61 mmol/g, respectively. In addition these adsorbentsare not containedfree SH-groups and chemically stable a longperiod oftime.TheN,S-containing silica sampleprepared by homogeneous procedure had 2 times higher adsorption capacity to ions Pd(II) than the sample by heterogeneous procedure.The results suggest that the prepared SiO2-SN(homo)adsorbent is potentially useful material for high effectively adsorption of metal ions from aqueous solution.
Keywords: N,S-containing silicas, conductometric titration, pH-metric titration, adsorption, silver, palladium